The inter-relationship between strategy, planning, plan in the field of S&T - Hoa, Nguyen Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Science and technology (S&T) strategy, planning, plan are always inter-related in respect of legislation, interaction, dependency and complementary to each other. They are intentionally formulated based on planned ideas. During the development of S&T policy, policy-makers always try to create a sustainable relationship among them, but to do that, there exist many difficulties encountered in reality. In this article, the author focused on research concerning theoretical bases, characteristics and rules of the relationship between S&T strategy, planning, plan to draw out from there a meaningful methodology.